Religious Conversion and Political Incorporation: An Event-Based Model of Immigrant Political Socialization - Andre P. Audette; Mark Brockway; Christopher L. Weaver (Religions)
Political socialization in the United States is circuitous and influenced by numerous outside sources, including parents, teachers, and peers. Moreover, civic organizations and political parties often work directly to recruit and mobilize citizens into politics. However, many foreign-born immigrants are denied these opportunities to acquire socialization. Immigrants are also often further overlooked or ignored by the civic and political organizations that incorporate most native-born Americans into politics. While a range of previous scholarship has sought to demonstrate and explain these disparities, few studies have examined alternative routes to political socialization or reconsidered the paradigm of incremental socialization as it applies to foreign-born populations. We argue that immigrants may instead become involved in the U.S. political system through religious conversion—a pivotal event in their lives. Using surveys of the two predominant U.S. immigrant groups, Asian Americans and Latinos, we show that religious conversion can catalyze the socialization process. Among both groups, religious conversion in the U.S. is associated with increased rates of political participation. These results suggest that immigrant socialization may follow different pathways than those of native-born populations, and that scholars should take into greater consideration the role of critical life events when modelling political socialization among foreign-born populations.